Real-Time Monitoring of ATG8 Lipidation in vitro Using Fluorescence Spectroscopy - Wenxin Zhang; Taki Nishimura; Sharon Tooze (Bio-Protocol, 2024)
Autophagy is an essential catabolic pathway used to sequester and engulf cytosolic substrates via a unique double-membrane structure, called an autophagosome. The ubiquitin-like ATG8 proteins play an important role in mediating autophagosome membrane expansion. They are covalently conjugated to phosphatidylethanolamine (PE) on the autophagosomes via a ubiquitin-like conjugation system called ATG8 lipidation. In vitro reconstitution of ATG8 lipidation with synthetic liposomes has been previously established and used widely to characterise the function of the E1 ATG7, the E2 ATG3, and the E3 complex ATG12–ATG5-ATG16L1. However, there is still a lack of a tool to provide kinetic measurements of this enzymatic reaction. In this protocol, we describe a real-time lipidation assay using NBD-labelled ATG8. This real-time assay can distinguish the formation of ATG8 intermediates (ATG7~ATG8 and/or ATG3~ATG8) and, finally, ATG8-PE conjugation. It allows kinetic characterisation of the activity of ATG7, ATG3, and the E3 complex during ATG8 lipidation. Furthermore, this protocol can be adapted to characterise the upstream regulators that may affect protein activity in ATG8 lipidation reaction with a kinetic readout.Key features• Preparation of ATG7 E1 from insect cells (Sf9 cells).• Preparation of ATG3 E2 from bacteria (E. coli).• Preparation of LC3B S3C from bacteria (E. coli).• Preparation of liposomes to monitor the kinetics of ATG8 lipidation in a real-time manner.Graphical overviewExperimental design to track the full reaction of ATG8 lipidation, described in this protocol